PERSPEKTIF YURIDIS TANGGUNG JAWAB DOKTER TERHADAP RAHASIA MEDIS PASIEN HIV/AIDS (Studi di Rumah Sakit Umum Daerah Banyumas) - Taufiq, Muhammad (Jurnal Dinamika Hukum, 2011)
Examination of HIV/AIDS patient with do voluntary and confidential principle. Patient confidentiality must be maintained with the best. Status and the presence of HIV/AIDS patients are kept secret and so raises dilemma for physicians nor patient themselves. Juridical perspective of physician responsibility in opening the medical secret of patients with HIV/AIDS is a view or understanding of legal liability physicians in opening the medical secret of HIV/AIDS patients. Things must be secret maintained in the form of of identity, diagnosis, disease history, inspection history and treatment history. Perspective juridical physician’s responsibility in RSUD Banyumas generally show very much agrees on opening medical confidential HIV/AIDS patients with patient consent. Implementation of medical confidentiality laws against HIV/AIDS patients in RSUD Banyumas implemented properly.Key words : confidential medical, legal perspectives physicians, law enforcement